1980
DOI: 10.1111/j.1748-1716.1980.tb06563.x
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the gastric glands and its relation to induced secretory activity of cod, Gadus morhua (Day)

Abstract: Light and electron microscopic studies have been performed on different parts of cod stomach. The studies have been concentrated on the gastric glands of the gastric mucosa. The glands consist of only one cell type. This cell contains an apically located, comprehensive tubular system as well as zymogen granules and therefore probably secretes both acid and zymogen. The high degree of development of certain organelles and their mutual localization shows a structural organization which appears suitable for an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Observation of the tract contents revealed that the major digestion of the engulfed prey and major absorption occurs in the stomach and the pyloric part of the intestine. Mattisson and Holstein (1980) and Osman and Caceti (1991), in contrast, described only one cell type in the digestive glands of the cod, Gadus morhua and of the cichlid, Oreochromis niloticus, respectively. As in other fishes, the digestive glands of the lizardfish are tubular, densely packed below the mucosa and opening as pits into the gut lumen (Elbal et al 1988;Gallagher et al 2001).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Observation of the tract contents revealed that the major digestion of the engulfed prey and major absorption occurs in the stomach and the pyloric part of the intestine. Mattisson and Holstein (1980) and Osman and Caceti (1991), in contrast, described only one cell type in the digestive glands of the cod, Gadus morhua and of the cichlid, Oreochromis niloticus, respectively. As in other fishes, the digestive glands of the lizardfish are tubular, densely packed below the mucosa and opening as pits into the gut lumen (Elbal et al 1988;Gallagher et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies of the alimentary tract in fishes have focused on a single species, such as Esox lucius by Bucke (1971); Gadus morhua by Mattisson and Holstein (1980), and Oreochromis niloticus (Tilapia) by Osman and Caceti (1991) and Morrison and Wright (1999), to mention only a few. Numerous studies of the alimentary tract in fishes have focused on a single species, such as Esox lucius by Bucke (1971); Gadus morhua by Mattisson and Holstein (1980), and Oreochromis niloticus (Tilapia) by Osman and Caceti (1991) and Morrison and Wright (1999), to mention only a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three agents carbachol, histamine, and 5-HT show that the cod stomach is capable of a differentiated output of acid and pepsin. This is worth pointing out, because in fish and other submammalian vertebrates, acid and pepsin are considered the products of the same, oxynticopeptic cell [39,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In fish, as well as in amphibians, reptiles and birds, the pepsinogens and hydrochloric acid are secreted by a single type of gastric cell known as the oxynticopeptic cell (Helander, 1981). This cell type in fish possesses certain structural characteristics common to both the peptic and oxyntic cells of mammals (Rebolledo & Vial, 1979;Mattisson & Holstein, 1980;Stroband & Kroon, 1981;Murray et al, 1994). The oxynticopeptic cell has been shown to secrete pepsinogens in some fish species (Reifel et al, 1985;Yasugi et al, 1988;Inui et al, 1995;Huang et al, 1998) and hydrochloric acid in others (Smolka et al, 1994), but none of these studies has demonstrated both functions in the same oxynticopeptic cell of a single species.…”
Section: Introductionmentioning
confidence: 99%